Consent in real estate development contracts - AMEL, BOUABDELLAH (The International tax journal, 2026)
Real estate development contracts are considered as named contracts to which the legislator has devoted specific provisions as well as general provisions, similar to other contracts. What distinguishes them is their subject matter, which concerns a property that has not yet been completed. Furthermore, the principle that “the contract is the law of the parties” is among the principles governing real estate development contracts. For the conclusion of this type of contract, it is necessary to meet the elements and requirements that ensure its validity, namely consent, object, cause, and formalities. Consent in these contracts has the characteristics of being future-oriented, which is the essence of the contract. Offer and acceptance take several forms, such as an invitation to contract. A sales contract may be a sale on credit or a contract to preserve a right. It requires sufficient legal capacity to act between its parties, with the will being free from defects.